2012
DOI: 10.1016/j.exer.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy harvesting site and distance from the explant affect conjunctival epithelial phenotype ex vivo

Abstract: The purpose of the study was to investigate if the number of goblet cells expanded ex vivo from a conjunctival explant is affected by the biopsy harvesting site on the conjunctiva and the distance from the explant. Conjunctival explants from six regions: superior and inferior bulbus, fornix, and tarsus of male Sprague–Dawley rats were grown in RPMI 1640 with 10% fetal bovine serum on coverslips for eight days. Histochemical and immunofluorescent staining of goblet (CK-7/UEA-1/1MUC5AC), stratified squamous, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In the He et al's study, we characterized the cells using the goblet cell‐specific cytokeratin (CK) 7 compared to the stratified squamous cell‐specific CK4 . In a previous study, we found that CK7 was the best way to identify goblet cells in actively proliferating and migrating cultures as goblet cells lose their secretory product including MUC5AC as they migrate and proliferate. Based on our previous work, we are confident that the cells growing on the MLD substrates are conjunctival epithelial cells that are most likely goblet cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the He et al's study, we characterized the cells using the goblet cell‐specific cytokeratin (CK) 7 compared to the stratified squamous cell‐specific CK4 . In a previous study, we found that CK7 was the best way to identify goblet cells in actively proliferating and migrating cultures as goblet cells lose their secretory product including MUC5AC as they migrate and proliferate. Based on our previous work, we are confident that the cells growing on the MLD substrates are conjunctival epithelial cells that are most likely goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of conjunctival epithelial stem cell deficiency, for example, following removal of extensive conjunctival tumors or chemical burns, cultured conjunctival transplants containing goblet cells can be used to restore the conjunctiva. As MLD substrates support the growth of goblet cells, this technique may potentially be used for production of goblet cell transplants …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations